Sarcopenia, functional capacity, and physical components of quality of life in older adults Mexicans: An explanatory model - Isaí Arturo Medina-Fernández; Sandra Cecilia Esparza-González; Nissa Yaing Torres Soto; Ana Laura Carrillo-Cervantes; Pedro Enrique Trujillo-Hernández; Josué Arturo Medina-Fernández (Journal of Research Development in Nursing and Midwifery)
Background: Sarcopenia, characterized by the progressive loss of muscle mass and strength, significantly impacts functional capacity and quality of life (QoL) in older adults. Among Mexican seniors, this condition exacerbates physical limitations, compromising daily activities and independence. The objective was to model the effect of sarcopenia on functional capacity and physical components of health-related QoL in older adults. Methods: The study has a predictive correlational design with a sample population of 144 older adults from Coahuila, Mexico in 2024. A demographic and clinical form was applied, containing measurements of calf circumference, body mass index (BMI), grip strength with a dynamometer, gait speed and appendicular skeletal muscle mass, simple questionnaire to rapidly diagnose sarcopenia, a subscale of physical components of the SF-36, Barthel Index for Activities of Daily Living (BADL), and Lawton-Brody scale. The data were analyzed with SPSS software version 20 using central tendency and dispersion, Kolmogorov Smirnov test, Mann Whitney U test, Spearman test, and simple linear regressions. Moreover, structural equation was assessed using EQS software version 6.1. Results: The results showed that the prevalence of sarcopenia was 44.8%, and sarcopenia significantly and negatively affected the basic activities of daily living (r=-0.46, p=0.001). In the same way, it negatively and significantly affected the instrumental activities of daily living (r=-0.41, p=0.001), meanwhile, it positively and significantly affected the physical components of quality of life (r=0.43, p=0.001). Conclusion: Therefore, it is concluded that sarcopenia negatively influences the physical components of QoL and functional capacity.